(untitled) (Revista de Psicología, 2021)
An important question in the well-being literature is how earning and spending money makes people happy. Some studies have shown that people are happier when earning money in constant payments, and spending money on significant others. However, some findings suggest that people with financial expertise may have different preferences based on the time value of money. The current study was designed to address this issue by asking both financial novices and financial experts if earning money at decreasing, constant or increasing rates would make them happier. By replicating and, more importantly, disambiguating previous findings, the results suggest that financial novices are happier when earning money in constant payments and spending money on debts, whereas financial experts are happier when earning money in decreasing payments and spending money on investments. These findings suggest that earning and spending money makes people happier in different ways depending on their financial expertise.